KNOWLEDGE MANAGEMENT SEBAGAI UPAYA PENGEMBANGAN LEARNING ORGANIZATION DI LEMBAGA PENDIDIKAN - Adi Putra (AN NUR: Jurnal Studi Islam, 2013)
The simple of the knowledge is the capacity take an action, so that knowledge is associate with five categories: Data, Information, Knowledge, Understanding, and Wisdom. The purpose of Knowledge Management there are three, namely: Business Vendor’s Perspective, Management prespective, and Hands-on operational perspective. There are two types of knowledge in organisation learning, first, Tacit knowledge. Second, Explicit Knowledge. And there are also Knowledge Management process in organisation learning; socialization, externalization, combination and internalization. There are also contributing factor in the success of Knowledge Management learning organization in educational institutions. First human factors, second factors of leadership, third technology, four organizations, and the fifth learning organization